“We Sometimes Hold on to Ours” – Professionals’ Views on Factors that both Delay and Facilitate Transition to Adult Care - Aldiss, Susie; Cass, Hilary; Ellis, Judith; Gibson, Faith (Frontiers in Pediatrics, 2016)
Background: The transition from child to adult services is a crucial time in the health of young people who may potentially fall into a poorly managed 'care gap'. Health service provision, which fails to meet the needs of young people and families at this time of significant change, may result in deterioration in health or disengagement with services, which can have negative long-term consequences. Developing transitional care packages has become a focus of activity in the United Kingdom and elsewhere. Indeed policy documents have been trying to guide practice for many years, with some variable success. There is much work still to be done, particularly around how guidance and sharing of best practice together can change practice. Objective: This study aimed to explore the views of professionals involved in transitional care, the process of transition in their services, the barriers and facilitators to transition. Methods: This was a qualitative study using focus group methodology. Four focus groups were carried out, attended by 36 health professionals across child and adult services. They had expertise in working with young people with various health conditions and disabilities. Transcripts were analysed using qualitative content analysis. Results: Eight key factors that impact on transition emerged from the data. These included factors associated with the patient group (such as age, health condition, having complex needs) as well as factors associated with services (such as the availability of equivalent services within adult care and the links between child and adult team). Conclusion: It is imperative professionals consider the population they are working with when planning transitional care and take into account the factors which can lead to delayed transition so that this can be avoided if possible. Numerous examples of initiatives to facilitate more timely transition were shared: these have been reflected in our ‘Benchmarks for Transition from Child to Adult Health Services’. We offer these benchmarks to inform and guide the practice of others, and illustrate their potential for use in the context of the findings shared here.